Correlation between activated partial thromboplastin time and diluted Russell’s viper venom time in the presence of lupus anticoagulant - Luz Tarín-Arzaga (Permanyer, 2021)
Lupus anticoagulant (LA) is a heterogeneous group of antibodies that interfere with phospholipid-dependent coagulation tests, which result in abnormally prolonged clotting times in vitro. The prevalence of LA in a healthy individual is 1-5%1,2.